2022
DOI: 10.1093/ajcn/nqab417
|View full text |Cite
|
Sign up to set email alerts
|

No additional benefit of prescribing a very low-protein diet in patients with advanced chronic kidney disease under regular nephrology care: a pragmatic, randomized, controlled trial

Abstract: Background Whether very low-protein diet supplemented with ketoanalogs (sVLPD), compared to standard low-protein diet (LPD), improves outcomes in chronic kidney disease (CKD) patients under stable nephrology care is undefined. Objective To compare the effectiveness of sVLPD vs LPD in patients regularly seen in tertiary nephrology care. Methods Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…In a further meta-analysis, a dietary protein intake <0.8 g protein/kg/day was found to have significant benefits on both GFR and proteinuria in early DKD [40]. Unfortunately, all the major RCTs on dietary protein intervention advanced CKD do not include diabetic patients [19]. This review provides some evidence that the decline in GFR may be attenuated in DKD patients who receive a KA-supplemented protein-restricted diet, as the meta-analysis showed a slight, nonsignificant increase in GFR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a further meta-analysis, a dietary protein intake <0.8 g protein/kg/day was found to have significant benefits on both GFR and proteinuria in early DKD [40]. Unfortunately, all the major RCTs on dietary protein intervention advanced CKD do not include diabetic patients [19]. This review provides some evidence that the decline in GFR may be attenuated in DKD patients who receive a KA-supplemented protein-restricted diet, as the meta-analysis showed a slight, nonsignificant increase in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mortality, Wang at al reported no difference between DKD patients who used KA and those who did not [29], and Chen et al showed a significantly lower all-cause mortality in KA users compared to non-users [26]. Whether LPD + KA in DKD patients does impact on mortality or not, as found in nondiabetic CKD [19,46], still needs to be explored. Overall, these differences were possibly due to major selection bias and highlight the need for RCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, one recent RCT performed by Bellizzi, V. et al, which enrolled patients with CKD stage 4 and stage 5, compared the long-term kidney and patient survival between patients that received sVLPDs and those that received LPD [ 18 ]. They found that the sVLPDs group did not have an additional advantage to the LPD group.…”
Section: Introductionmentioning
confidence: 99%